Adverse Events Following Daily Steroid Therapy in Children with First Episode of Minimal Change Nephrotic Syndrome - Rahman, Ashikabanu Mujibur; Sugumar, Ashwathi; Ramesh, Shivani (Journal of Neonatal Surgery, 2025)
Background: Minimal change nephrotic syndrome (MCNS) remains the most common glomerular disorder in children, often exhibiting a favourable response to corticosteroids. Despite high remission rates, the treatment course is marred by a spectrum of steroid-associated complications that affect both physiological and psychosocial well-being. Aim of the Study: To assess the frequency and profile of adverse events during daily steroid induction therapy among children presenting with their first episode of MCNS. Methods: This observational study consolidates data from five recent clinical trials and cohort studies focusing on steroid-induced adverse effects in paediatric MCNS. Data on seven predefined complications, obesity, hypertension, hyperglycaemia, behavioural changes, growth delay, cataract formation, and infections, were extracted and systematically analysed. Only studies involving daily prednisolone/prednisone induction (4–6 weeks) in first-episode steroid-sensitive nephrotic syndrome (SSNS) were included. Results: Across the pooled cohort (n = 763), obesity or significant weight gain was noted in up to 31% of children during the induction phase. Behavioural disturbances were recorded in approximately 27%, while transient hypertension occurred in 13% of cases. Other events included hyperglycaemia (9.4%), growth retardation (17.8%), subcapsular cataract formation (11.2%), and documented infections (12.5%), including upper respiratory tract infections and superficial skin abscesses. No mortality or steroid-resistant transition was observed during the initial 8-week period. Children receiving six-week courses did not experience significantly fewer relapses but displayed comparable adverse event rates. Conclusion: While corticosteroid therapy remains the mainstay for MCNS induction in children, the adverse effects, though generally reversible, present substantial short-term morbidity. Periodic screening for behavioural, metabolic, and ophthalmic complications during therapy is recommended to minimise cumulative harm